The Critical Role of Academic Clinical Trials in Pediatric Cancer Drug Approvals: Design, Conduct, and Fit for Purpose Data for Positive Regulatory Decisions. Issue 29 (10th October 2022) - De Wilde, Bram; Barry, Elly; Fox, Elizabeth; Karres, Dominik; Kieran, Mark; Manlay, John; Ludwinski, Donna; Reaman, Gregory; Kearns, Pamela
Abstract : PURPOSE: For decades, academic clinical trials consortia have collaborated to optimize outcomes for childhood cancers through evaluating incremental improvements in conventional mutimodality treatment regimes. There are now increasing opportunities to partner with industry to test new medicines in academic-sponsored trials, but these collaborative studies rarely contribute to marketing authorizations. We addressed why this is the case and sought solutions to enable academic-sponsored trials to directly contribute to the licensing of new medicines. METHODS: Under the auspices of the multistakeholder platform ACCELERATE, we convened a working group of representatives from clinical academia, pharmaceutical industry, European Medicines Agency, US Food and Drug Administration, and patient advocacy to define the challenges and propose recommendations to facilitate academic-sponsored trial design and conduct to be aligned to both the needs of the pharmaceutical company who own the asset and the expectations of the regulatory (licensing) authorities. RESULTS: We identified that although academic consortia have long-standing expertise to conduct robust clinical trials, there were critical gaps in knowledge, standard procedures, and resources that hindered the trial data directly contributing to marketing authorization applications. We propose a suite of recommendations focused on (1) essential documents, (2) essential data, (3) data management, and (4) trial resources, specifically aimed at enabling academic-industry partnerships to deliver an academic-sponsored trial that meets the requirements for a marketing authorization submission. These recommendations pivot around transparency in academic-industry partnerships and early engagement with regulators. CONCLUSION: Academic sponsors and industry partners need to prospectively recognize when the planned collaborative trial could contribute to an application to marketing authorization and plan accordingly. Transparent collaboration and knowledge sharing between the partners opens an important pathway for accelerating new treatments into clinical practice for children with cancer.